Online Journal of Mathematics, Science and Technology Education (OJOMSTE) Vol:6 No:1(2025)-June 2025 - TUNA, Abdulkadir; Akyüz, Halil İbrahim (Halil İbrahim AKYÜZ, 2025)
This journal aims to publish original, fully peer-reviewed articles on various topics and research methods in science, mathematics and technology education. The journal welcomes articles that address common topics and cross-curricular dimensions in mathematics, science, and technology education in a broader sense. Contemporary educators emphasize the importance of seeing knowledge as context-oriented, not limited to a single field. It welcomes studies that deal with theoretical, experimental, qualitative, quantitative methods and examine from different cultural perspectives on the integration and use of modern educational practices in Mathematics, Science, and technology education curricula. The Online Journal of Mathematics,  Science and Technology Education provides a medium by which a wide range of experience in mathematics education, Science Education, and Technology education can be presented, assimilated and eventually adapted to everyday needs in schools, colleges, polytechnics, universities, industry and commerce. Contributions will be welcomed from lecturers, teachers and users of Technology at all levels on the contents of syllabuses and methods of presentation. Increasing use of technology is being made in the teaching, learning, assessment, and presentation of mathematics and Science today; original and interesting contributions in this rapidly developing area will be especially welcome. Mathematical and Science models arising from real situations, the use of computers, new teaching aids, and techniques also form an important feature. Discussion will be encouraged on methods of widening applications throughout science and technology. The need for communication between teacher and user will be emphasized and reports of relevant conferences and meetings will be included.